2015
DOI: 10.1111/are.12712
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary protein and lipid levels on growth, body composition and flesh quality of juvenile topmouth culter,Culter alburnusBasilewsky

Abstract: Nine experimental diets at three protein (35%, 40% and 45% crude protein) and lipid (5%, 8% and 11% crude lipid) levels with variable digestible protein to digestible energy (DP/DE) ratios ranged from 21.9 to 27.8 g protein MJ−1 were fed to topmouth culter (Culter alburnus Basilewsky) fingerlings (initial weight 6.5 ± 0.9 g) in triplicated groups (30 fish per replicated) for a period of 10 week to assess the optimum dietary DP/DE ratio and the protein sparing effect by utilizing dietary lipid. 27 cages of 1.5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 28 publications
7
7
0
Order By: Relevance
“…Furthermore, the optimum dietary protein requirement for maximum growth was 39.08% of the dry‐matter basis (Figure ). This result was similar to the protein requirement of the tropical bagrid catfish Horabagrus brachysoma (39.1%) (Giri, Sahoo, Paul, Mohanty, & Sahu, ) and Mystus nemurus (40%) (Ng, Soon, & Hashim, ), and juvenile Culter alburnus (40%) (Zhang et al, ). However, the protein requirement assessed in this study was smaller than those previously reported in M. albus juveniles, whose protein/lipid ratio were 420/55 g/kg (body weight of 37.83–39.75 g) (Chen et al, ) and 450/40 g/kg (body weight of 65.76 ± 1.07 g) (Ma et al, ) respectively.…”
Section: Discussionsupporting
confidence: 77%
“…Furthermore, the optimum dietary protein requirement for maximum growth was 39.08% of the dry‐matter basis (Figure ). This result was similar to the protein requirement of the tropical bagrid catfish Horabagrus brachysoma (39.1%) (Giri, Sahoo, Paul, Mohanty, & Sahu, ) and Mystus nemurus (40%) (Ng, Soon, & Hashim, ), and juvenile Culter alburnus (40%) (Zhang et al, ). However, the protein requirement assessed in this study was smaller than those previously reported in M. albus juveniles, whose protein/lipid ratio were 420/55 g/kg (body weight of 37.83–39.75 g) (Chen et al, ) and 450/40 g/kg (body weight of 65.76 ± 1.07 g) (Ma et al, ) respectively.…”
Section: Discussionsupporting
confidence: 77%
“…The gonadal development in fish is closely associated with the ecological conditions. In fish, when the dietary protein and lipid requirements are not fulfilled, it can lead to metabolic disorder (Zhang et al., ). In the present study, the dietary protein and lipid levels did not affect the female GSI significantly ( p > 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…The reactive oxygen species (ROS) generated by lipid peroxidation can result in damage to tissues and cellular integrity, and MDA is a main marker of oxidative damage induced by ROS (Rueda‐Jasso et al ; Zhang et al ). In the present study, fish fed high lipid diets (L8.5 and L10) had the highest MDA contents in hepatopancreas and intestine of G. przewalskii .…”
Section: Discussionmentioning
confidence: 99%